ANALISIS RELATIONSHIP MARKETING DAN PROMOSI DALAM MENINGKATKAN KEPUASAN KONSUMEN UMKM KULINER KOTA MEDAN - Nicholas Adinata Kisono; Hommy Dorthy Ellyany Sinaga; Rahmad Dianta Purba (PT. Hasba Edukasi Mandiri, 2026)
This study aims to describe the influence of relationship marketing and promotion on consumer satisfaction in culinary MSMEs in Medan City. The research background highlights the rapid growth of culinary businesses and intense competition, requiring entrepreneurs to rely not only on product quality but also on marketing strategies that foster consumer loyalty. Relationship marketing emphasizes communication, service, and trust, while promotion introduces products, increases sales, and builds brand image through discounts, bundling packages, social media, and influencer collaborations. A descriptive approach was applied, using observation, interviews, and literature review. Findings reveal that relationship marketing enhances consumer satisfaction through personal interaction and friendly service, while promotion provides added value via affordable pricing and emotional engagement. The synergy of both strategies creates stronger effects: promotion attracts new consumers, while relationship marketing ensures existing ones remain loyal. In conclusion, combining effective promotional strategies with consistent relationship marketing is essential for culinary MSMEs in Medan to achieve consumer satisfaction and strengthen competitiveness.